Development of a syngeneic mouse model of epithelial ovarian cancer - Quinn Bridget A; Xiao Fang; Bickel Laura; Martin Lainie; Hua Xiang; Klein-Szanto Andres; Connolly Denise C (BMC, 2010)
Abstract Background Most cases of ovarian cancer are epithelial in origin and diagnosed at advanced stage when the cancer is widely disseminated in the peritoneal cavity. The objective of this study was to establish an immunocompetent syngeneic mouse model of disseminated epithelial ovarian cancer (EOC) to facilitate laboratory-based studies of ovarian tumor biology and preclinical therapeutic strategies. Methods Individual lines of TgMISIIR-TAg transgenic mice were phenotypically characterized and backcrossed to inbred C57BL/6 mice. In addition to a previously described line of EOC-prone mice, two lines (TgMISIIR-TAg-Low) were isolated that express the oncogenic transgene, but have little or no susceptibility to tumor development. Independent murine ovarian carcinoma (MOVCAR) cell lines were established from the ascites of tumor-bearing C57BL/6 TgMISIIR-TAg transgenic mice, characterized and tested for engraftment in the following recipient mice: 1) severe immunocompromised immunodeficient (SCID), 2) wild type C57BL/6, 3) oophorectomized tumor-prone C57BL/6 TgMISIIR-TAg transgenic and 4) non-tumor prone C57BL/6 TgMISIIR-TAg-Low transgenic. Lastly, MOVCAR cells transduced with a luciferase reporter were implanted in TgMISIIR-TAg-Low mice and in vivo tumor growth monitored by non-invasive optical imaging. Results Engraftment of MOVCAR cells by i.p. injection resulted in the development of disseminated peritoneal carcinomatosis in SCID, but not wild type C57BL/6 mice. Oophorectomized tumor-prone TgMISIIR-TAg mice developed peritoneal carcinomas with high frequency, rendering them unsuitable as allograft recipients. Orthotopic or pseudo-orthotopic implantation of MOVCAR cells in TgMISIIR-TAg-Low mice resulted in the development of disseminated peritoneal tumors, frequently accompanied by the production of malignant ascites. Tumors arising in the engrafted mice bore histopathological resemblance to human high-grade serous EOC and exhibited a similar pattern of peritoneal disease spread. Conclusions A syngeneic mouse model of human EOC was created by pseudo-orthotopic and orthotopic implantation of MOVCAR cells in a susceptible inbred transgenic host. This immunocompetent syngeneic mouse model presents a flexible system that can be used to study the consequences of altered gene expression (e.g., by ectopic expression or RNA interference strategies) in an established MOVCAR tumor cell line within the ovarian tumor microenvironment and for the development and analysis of preclinical therapeutic agents including EOC vaccines and immunotherapeutic agents.